HUBUNGAN KEIKUTSERTAAN ORGANISASI IPNU IPPNU KOMISARIAT TERHADAP PRESTASI NON AKADEMIK PESERTA DIDIK - Khubni Maghfirotun; Ahmad Bashory Alwy (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
This study discusses the Relationship of the Commissariat IPNU IPNU to the Non-Academic Achievement of Class XI in SMK Wachid Hasjim Maduran 2019. This research purpose to: (1) the IPNU IPPNU Commissariat Organization performs in improving Non-Academic Achievement. (2) the level of participation of IPNU IPPNU Commissariat Organizations in increasing Non-Academic Achievement, (3) Is there any influence of IPNU IPNU Commisariat Organizational Organization in improving Non Academic Achievement in Class XI at SMK Wachid Hasjim Maduaran. This research is quantitative research. The population was 85 and 65 samples were taken. Data collection used a questionnaire distributed via Google From to determine the Participation of IPNU IPPNU Commissariat Organization on Non Academic Achievement. Data that has been collected is then analyzed using the product moment correlation of this study showing that: (1) The implementation of the IPNU IPPNU Commissariat Organization in increasing Non Academic Achievement is good, there are several activities aimed at honing Non Academic abilities of students at SMK Wachid Hasjim Maduran. (2) The level of participation of students in class XI Wachid Hasjim Vocational School with a percentage of 59.73% results in the category of not good. while the non-academic pretension of Class XI of SMK Wachid Hasjim Maduran is in the percentage of 70.73% in the good category. (3) There is a relationship between IPNU IPPNU Commissariat Organization's Commitment to Non Academic Achievement in Class XI of SMK Wachid Hasjim Maduran in 2019. This is evidenced by the calculation of Product Moment Correlation stating that r Count (rxy) = 0.726 then matched with rtabel grade 5% with respondents 655. = 0.244. Thus it can be seen that the r count is greater than r table then the alternative hypothesis is accepted that there is a relationship of IPNU IPPNU Commisariat Organizational Organization to Non Academic Achievement in the XI grade of SMK Wachid Hasjim Maduran in 2019.